Relationship of Ferritin Levels of Pregnant Women Who Had Fe Deficiency Anemia with Ferritin Levels and APGAR of the Neonates - Zuliyana Zuliyana; Yanwirasti Yanwirasti; Roza Sri Yanti (Journal of Midwifery, 2018)
Iron deficiency anemia in pregnant women can have a negative impact on the baby, such as placental development, low birth weight, prematurity, baby health, hypoxia, decreased immune status, possibility of having physiological disorders and infant growth. The aim of this study was to determine the relationship of ferritin levels of pregnant women who had Fe deficiency anemia with ferritin levels and Apgarof the neonates.This was a cross sectional study in the population of pregnant women who had Fe deficiency anemia and neonates who met the inclusion criteria taken by consecutive sampling technique in the working area of Lubuk Buaya Health Center, Ambacang Health Center and Ikur Koto Health Center. Examination of ferritin levels was carried out in the Biomedical Laboratory of  Faculty of Medicine, Andalas University using ELISA method. Data were analyzed by Pearson Test and Mann-Whitney Test.  The results of this study showed there was no significant relationship between maternal ferritin levels on neonatal ferritin r = 0.248, p = 0.204. It also showed that there was no relationship between maternal ferritin levels on APGAR p value = 0.199 and there was a significant relationship between neonatal ferritin levels on APGAR p value = 0.002. The conclusion of this study is that there was a positive relationship between maternal ferritin levels with neonatal ferritin levels, there was no significant relationship between maternal ferritin levels and APGAR score, there is a significant relationship betweenneonatal ferritin levels with APGAR score. By improving nutrition, socioeconomic, qualitative antenatal care, early referral of risky cases and iron supplementation can reduce the incidence of anemia.